2009
DOI: 10.1007/s00395-009-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscarinic receptor stimulation on Ca2+ transient, cAMP production and pacemaker frequency of rabbit sinoatrial node cells

Abstract: We investigated the contribution of the intracellular calcium (Ca transients (Indo-1 fluorescence) were recorded from single isolated rabbit SAN cells, whereas intracellular cAMP content was measured in SAN cell suspensions using a cAMP assay (LANCE Ò

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 53 publications
5
50
0
Order By: Relevance
“…54) have been mainly based on a H-H-type membrane voltage oscillator, the present numerical study revealed that the rate of spontaneous APs in cardiac pacemaker cells is modulated by GPCR signaling via a complex dynamic integration of voltage-and Ca 2ϩ -dependent processes within the SANC system (Fig. 8), consistent with experimental results (32,47,49,50,55) and recent reviews (27,34). The shifts (marked by ⌬) in the balance of system components (which ultimately determine the chronotropic response) are looped and are thus interdependent.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…54) have been mainly based on a H-H-type membrane voltage oscillator, the present numerical study revealed that the rate of spontaneous APs in cardiac pacemaker cells is modulated by GPCR signaling via a complex dynamic integration of voltage-and Ca 2ϩ -dependent processes within the SANC system (Fig. 8), consistent with experimental results (32,47,49,50,55) and recent reviews (27,34). The shifts (marked by ⌬) in the balance of system components (which ultimately determine the chronotropic response) are looped and are thus interdependent.…”
Section: Discussionsupporting
confidence: 87%
“…Previous experimental results (32,47) have shown that the mechanism of SANC rate slowing via ChR activation is complex and includes changes in both sarcolemmal ion currents and diastolic Ca 2ϩ release. Electrophysiological changes include PKA-dependent I CaL reduction (43,56), a shift of cAMPdependent I f activation toward negative potentials (9, 10), and G i -dependent activation of I KACh (6, 12) (Fig.…”
Section: Prediction Of Chr Stimulationmentioning
confidence: 99%
“…Parasympathetic tone is regulated by cholinergic signaling, which affects pacemaker function, enhances pacemaker shifting, slows the HR by altering the hyperpolarization-activated cation current (I f ) and the muscarinic receptor activated K + current (I K,Ach ), and reduces Ca 2+ transients (24)(25)(26). We next examined whether deletion of STIM1 altered the sensitivity of the SAN in response to cholinergic stimulation.…”
Section: Significancementioning
confidence: 99%
“…Both currents are involved in heart's pacemaker activity and they are regulated by muscarinic receptors [19]. I KACh currents are activated by Gi-coupled M2/M4 muscarinic receptor, where Gi protein directly opens K +1 channels [20].…”
Section: Discussionmentioning
confidence: 99%